Genetic Basis of Extramedullary Plasmablastic Transformation of Multiple Myeloma. (June 2020) - Liu, Ying; Jelloul, Fatima; Zhang, Yanming; Bhavsar, Tapan; Ho, Caleb; Rao, Mamta; Lewis, Natasha E.; Cimera, Robert; Baik, Jeeyeon; Sigler, Allison; Sen, Filiz; Yabe, Mariko; et al.
Abstract : In patients with multiple myeloma, plasmablastic transformation in the bone marrow is rare and associated with poor outcomes. The significance of discordant extramedullary plasmablastic transformation in patients with small, mature clonal plasma cells in the bone marrow has not been well studied. Here, we report the clinicopathologic, cytogenetic, and molecular features of 10 such patients (male/female: 6/4, median age: 65 y, range: 48 to 76 y) with an established diagnosis of multiple myeloma in the bone marrow composed of small, mature plasma cells in parallel with a concurrent or subsequent extramedullary plasmablastic transformation. Eight patients with available survival data showed an overall aggressive clinical course with a median survival of 4.5 months after the diagnosis of extramedullary plasmablastic transformation, despite aggressive treatment and even in patients with low-level bone marrow involvement. Pathologically, the extramedullary plasmablastic myeloma were clonally related to the corresponding bone marrow plasma cells, showed high levels of CMYC and/or P53 expression with a high Ki-67 proliferation index by immunohistochemistry and harbored more complex genomic aberrations including frequent mutations in the RAS pathway and MYC rearrangements compared with their bone marrow counterparts. In summary, although genetic and immunohistochemical studies were not uniformly performed on all cases due to the retrospective nature of this study, our data suggest that discordant extramedullary plasmablastic transformation of multiple myeloma has an aggressive clinical course and is characterized by frequent mutations in the RAS pathway and more complex genomic abnormalities.